A fractionally cointegrated VAR analysis of economic voting and political support - Maggie E. C. Jones; Morten Ørregaard Nielsen; Michał Ksawery Popiel (Queen's University, Department of Economics, 2014)
We use a fractionally cointegrated vector autoregressive model to examine the relationship between Canadian political support and macroeconomic conditions. This model is well suited for the analysis because it allows multiple fractional time series and admits simple asymptotic inference for the model parameters and tests of the hypotheses of interest. In the long-run equilibrium, we find that support for the Progressive Conservative Party was higher during good economic times, i.e. periods of high interest rates and low unemployment, while support for the Liberal Party was higher during bad economic times, i.e. periods of low interest rates and high unemployment. We also test and reject the notion that party support is driven only by relative (to the United States) economic performance. Indeed, our findings suggest that US macroeconomic variables do not enter the long-run equilibrium of Canadian economic voting (political opinion poll support) at all.
Keywords: C32; D72; 330; economic voting; fractional cointegration; political economy; vector autoregressive model